Variation in APOL1 Contributes to Ancestry-Level Differences in HDLc-Kidney Function Association - Amy Rebecca Bentley; Ayo P. Doumatey; Guanjie Chen; Hanxia Huang; Jie Zhou; Daniel Shriner; CongQing Jiang; Zhenjian Zhang; Guozheng Liu; Olufemi Fasanmade; Thomas Johnson; Johnnie Oli; et al. (International Journal of Nephrology)
Low levels of high-density cholesterol (HDLc) accompany chronic kidney disease, but the association between HDLc and the estimated glomerular filtration rate (eGFR) in the general population is unclear. We investigated the HDLc-eGFR association in nondiabetic Han Chinese (HC, n=1100), West Africans (WA, n=1497), and African Americans (AA, n=1539). There were significant differences by ancestry: HDLc was positively associated with eGFR in HC (β=0.13, P<0.0001), but negatively associated among African ancestry populations (WA: −0.19, P<0.0001; AA: −0.09, P=0.02). These differences were also seen in nationally-representative NHANES data (among European Americans: 0.09, P=0.005; among African Americans −0.14, P=0.03). To further explore the findings in African ancestry populations, we investigated the role of an African ancestry-specific nephropathy risk variant, rs73885319, in the gene encoding HDL-associated APOL1. Among AA, an inverse HDLc-eGFR association was observed only with the risk genotype (−0.38 versus 0.001; P=0.03). This interaction was not seen in WA. In summary, counter to expectation, an inverse HDLc-eGFR association was observed among those of African ancestry. Given the APOL1 × HDLc interaction among AA, genetic factors may contribute to this paradoxical association. Notably, these findings suggest that the unexplained mechanism by which APOL1 affects kidney-disease risk may involve HDLc.